Investigating the association between children's screen media exposure and vocabulary size in the UK. Issue 1 (2nd January 2018) - Taylor, Gemma; Monaghan, Padraic; Westermann, Gert
Abstract: Children are growing up in a digital age with increasing exposure to television and touchscreen devices. We tested whether exposure to screen media is associated with children's early language development. One hundred and thirty-one highly educated caregivers of UK children aged 6–36 months completed a media exposure questionnaire and vocabulary measure. 99% of children were read to daily, 82% watched television, and 49% used mobile touchscreen devices daily. Regression analyses revealed that time spent reading positively predicted vocabulary comprehension and production scores at 6–18 months, but time spent engaging with television or mobile touchscreen devices was not associated with vocabulary scores. Critically, correlations revealed that time spent reading or engaging with other non-screen activities was not offset by time spent engaging with television or mobile touchscreen devices. Thus, there was no evidence to suggest that screen media exposure adversely influenced vocabulary size in our sample of highly educated families with moderate media use.